Etnosains Tanaman Nyamplung (Chalophyllum inophillum L.) dalam Tradisi Masyarakat Sasak - Khery, Yusran; Sarjan, Muhammad; Nufida, Baiq Asma; Efendi, Ismail (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
Nyamplung tree (Chalophyllum inophillum L.) in the tradition of Sasak people known as raq amterial for making Dile Jojor and medicines. Behind the traditions, learning about Nyamplung ethnosciece can provide more meaningful science learning experience. Through literature study, this article describes ethnoscience of Nyamplung and aspects of science related to it. Nyamplung was potential row materials for renewable fuels, medicines and cosmetics, pest and pollution control, and ecosystem conservation. Learning about the proper use of Nyamplung may cause good impact either to leraning quality, community welfare, and environmental conservation.